James Henry Hammond papers - Hammond, James Henry, 1807-1864.; McLean, Andrew
Correspondence, diaries, speeches, plantation manuals, account books, and scrapbooks pertaining chiefly to South Carolina and national politics in the decades preceding the Civil War. Subjects include nullification, secession, slavery, the Southern Convention at Nashville, Tenn. (1850), state banks, states' rights, and the tariff. Diary notes and memoranda cover the period of Hammond's travels in America and abroad, and plantation books contain memoranda of crops to be planted, lists of blacks, and notes on management of slaves. Also includes a mercantile letterbook (1774-1780) of Andrew McLean containing letters written from Savannah and Augusta, Ga., to Clark & Milligan, London, England.
Correspondents include A. P. Aldrich, Bert Alvord, Lewis M. Ayer, Ker Boyce, Abbot H. Brisbane, Pierce Mason Butler, John C. Calhoun, James L. Clark, John Myers Felder, James Gadsden, James Hamilton, Isaac W. Hayne, Robert Young Hayne, Lawrence M. Keitt, George McDuffie, Angus Patterson, A. H. Pemberton, Francis W. Pickens, Wm. D. Porter, William C. Preston, Paul Quattlebaum, Robert Barnwell Rhett, William Gilmore Simms, William Henry Trescot, Ben Tucker, and James M. Walker.
Microfilm edition, with the exception of the printed material in container 50, available
Microfilm produced from originals in Manuscript Division.
U.S. senator from and governor of South Carolina and plantation owner.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Aldrich, A. P. -- Correspondence; Alvord, Bert -- Correspondence; Ayer, Lewis M. -- Correspondence; Boyce, Ker -- Correspondence; Brisbane, A. H. -- 1804-1861 -- Correspondence; Butler, Pierce Mason, -- 1798-1847 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Clark, James L. -- Correspondence; Felder, John Myers, -- 1782-1851 -- Correspondence; Gadsden, James, -- 1788-1858 -- Correspondence; Hamilton, James, -- 1786-1857 -- Correspondence; Hayne, Isaac W. -- 1809-1880 -- Correspondence; Hayne, Robert Young, -- 1791-1839 -- Correspondence; Keitt, Lawrence M. -- 1824-1864 -- Correspondence; McDuffie, George, -- 1790-1851 -- Correspondence; Patterson, Angus -- Correspondence; Pemberton, A. H. -- Correspondence; Pickens, F. W. -- 1805-1869 -- Correspondence; Porter, Wm. D. -- 1810-1883 -- Correspondence; Preston, William C. -- 1794-1860 -- Correspondence; Quattlebaum, Paul, -- 1812-1890 -- Correspondence; Rhett, Robert Barnwell, -- 1800-1876 -- Correspondence; Simms, William Gilmore, -- 1806-1870 -- Correspondence; Trescot, William Henry, -- 1822-1898 -- Correspondence; Tucker, Ben -- Correspondence; Walker, James M. -- 1813-1854 -- Correspondence; Banks and banking -- Southern States; Business records; Nullification (States' rights); Plantations; Secession; Slavery -- United States; States' rights (American politics); Tariff -- United States; South Carolina -- Politics and government -- 1775-1865.; United States -- Politics and government -- 1815-1861.; Governors -- South Carolina; Plantation owners; Senators, U.S. Congress -- South Carolina